Tandem-column extraction chromatography for Nd separation: minimizing mass-independent isotope fractionation for ultrahigh-precision Nd isotope-ratio analysis. Issue 1 (21st December 2021) - Wang, Da; Carlson, Richard W.
Abstract : A new rapid and effective Nd separation scheme for 142 Nd/ 144 Nd isotope ratio measurement is shown to have no detectable mass-independent isotope fractionation. Abstract : The short-lived 146 Sm– 142 Nd isotope system traces key early planetary differentiation processes that occurred during the first 500 million-years of the solar system history. The variations of 142 Nd/ 144 Nd in terrestrial samples, typically within a range of ±20 ppm, are determined using high-precision mass spectrometry that requires quantitative separation of Nd from all other elements in the sample, including the neighboring lanthanides. Recent improvements in mass spectrometry have pushed the analytical precision of 142 Nd/ 144 Nd measurements down to ∼2 ppm. Non-mass-dependent isotope fractionation produced during Nd separation, however, is a major factor limiting the quality of the 142 Nd data. Popular chemical separation methods using Ln resins have unpredictable nuclear field shift effects that generate anomalous Nd isotope ratios. In order to solve this problem and potentially resolve small 142 Nd/ 144 Nd variations within ±5 ppm, in this study, we present a new two-step column separation method that effectively removes the isobaric interferents of Ce, Pr and Sm, with a recovery rate of Nd greater than 98%. JNdi-1 standard solutions doped with these interfering elements and geological reference materials are tested to document the performance of this method. A set of titanite samples from the Pilbara Craton in western Australia were also investigated to test the potential isotope fractionation effects. The same samples were processed using our method and the widely used Ln method. In contrast to the nuclear field shift effects observed from the samples using the Ln method, the results based on our new method show no detectable isotope fractionation, which further confirms the reliability of this new column chemistry scheme that is optimized for ppm-level precision Nd isotope ratio measurement, especially for resolving small variations in 142 Nd/ 144 Nd caused by the decay of 146 Sm.